PENGARUH SISTEM PENGENDALIAN MANAJEMEN DAN PENGENDALIAN INTERNAL TERHADAP KINERJA PERUSAHAAN (STUDI KASUS PADA PT. GEO-ENVIRO ABADI CONSULTAN & ENGINERING SURABAYA) - Noneng R. Sukatmadiredja (Media Mahardhika, 2021)
This research aims to determine the influence of management control system and internal control on the company's performance in PT. Geo-Enviro Abadi Consultan &Enginering Surabaya. Data collection using survey method through questionnaire dissemination. Sample techniques using purposive sampling amounted to 32 respondents who were distributed to accounting departments and employees who participated in the field of budgeting in the pt company area. Geo-Enviro Abadi Consultan &Enginering Surabaya. The data analysis method used is quantitative analysis using validity, reliability, classic assumption test, and double barg linear regression. The results showed that the validity test showed all items with a validity value of > from 0.3024, the reliability test results of all reliable variables with a > of 0.60, classic assumption test results of both normality, heterokedastity test and multicolinnerity test showed all results showed no conflicting symptoms and all items were normally distributed. Partial tests showed that the influence of internal control on the Company's performance had a significant positive effect with a significance of 0.002 of 3,463 influences and Management Control on the Company's performance, had an insignificant effect with a significance of 0.609> from 0.005, simultaneously.F test results showed that internal Management and Control Control had a significant effect of 0.003 with an influence of 7,384 on the company's Performance.